Fungicidal spray schedule for the economical management of pea powdery mildew - B.R. THAKUR, A.S. KAPOOR and (Indian Phytopathology, 2002)
During 1991, triadimefon (as Bayleton 25 WP), carbendazim (as Bavistin 50 WP), dinocap (Karathane 48 EC) and sulfur (as Wettasul 80 WP) were evaluated in different combinations for their effectiveness in controlling pea infection by Erysiphe pisi in Himachal Pradesh, India. All combinations of systemic and protectant fungicides significantly controlled the disease.